Four-terminal resistance in a clean interacting quantum wire with invasive contacts - Aita, Hugo Alberto (2012)
We investigate the behavior of the four-terminal resistance R4 pt in an interacting quantum wire described by a Luttinger liquid with an applied bias voltage V and coupled to two voltage probes. We extend previous results, obtained for very weakly coupled contacts, to the case in which the effects of the probes become non-trivially correlated. © 2012 Elsevier B.V.